Lipid dysregulation in Tangier disease: a case series and metabolic characterization - Semmler, Georg; Baumgartner, Clemens; Metz, Matthäus; Gensluckner, Sophie; Habisch, Hansjörg; Hofer, Hannah; März, Winfried; Offner, Felix; Völkerer, Andreas; Petrenko, Oleksandr; Wernly, Bernhard; Draxler-Dworzak, Sophie; et al. (The journal of clinical endocrinology & metabolism, 2025)
Tangier disease (TD) is a rare, autosomal recessive genetic disorder associated with a deficiency in cellular cholesterol export leading to cholesterol accumulation in peripheral tissues. With approximately 150 described cases, the disease is significantly understudied, and the clinical presentation appears to be heterogenous.To investigate the phenotype and lipid metabolism in TD.Multicenter cohort study.Four patients with TD.Nuclear magnetic resonance (NMR)-based lipidomic and metabolomic analyses were performed in patients with TD and healthy controls.While showing similar laboratory patterns with respect to high-density lipoprotein (HDL) depletion, the clinical presentation of 4 TD patients was heterogenous with 2 patients diagnosed at 47 and 72 years having predominantly gastrointestinal and neurological phenotypes. Two previously undescribed variants (c.2418G > A, c.5055.del) were reported.Apart from pathognomonic changes in HDL composition, NMR spectroscopy revealed an increased abundance of very low-density lipoprotein (VLDL) with higher total lipid and cholesterol concentrations, pointing toward an impaired clearance of triglyceride-rich lipoproteins. Increased triglyceride-rich intermediate-density lipoprotein supports impaired hepatic lipase activity, together with a cholesteryl ester transfer protein-mediated increase in low-density lipoprotein (LDL)-triglycerides at higher abundance of large LDL subtypes and decreased small dense LDL.The lipid composition of HDL particles and LDL-1/LDL-4 remained the strongest differentiating factors as compared to healthy controls.Clinical phenotypes of TD can be heterogeneous including gastrointestinal and neurological manifestations. Impaired triglyceride-rich lipoprotein clearance and hepatic lipase activity could be a pathophysiological hallmark of TD.